Philosophy and Theology Based on the Philosopher Réne Girard: A Reflection - Dogi Angga Saputra; Flora Pransiska; Jesicka Agustiana; Remikariasa; Rika; Selma Veronika (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine in a simple way when talking about Réne Girard's mimetic desire to be connected with narratives of sacrifice that are synonymous with violence, especially—besides speaking in other scientific disciplines—theology in the narratives of the Judeo-Christian scripture tradition. This research uses qualitative research methods with literature study. Literature study by looking at the interplay of philosophy and theology through the lens of Réne Girard. The results of the research show that there is a rationalization/perpetuation of violence through narration to practice, both within the state, the church and in the holy texts themselves. Through the light of the mimetic desire in the narrative of Yusuf and his brothers and the narrative of King Solomon and his two wives who claim children born from their respective wombs, it shows that 2 of the many texts which are patterned on characterizing violence are identical to these praxis-narratives.